DEFINISI EVALUASI DALAM KONTEKS SENI TARI - Aditia Aji Pangestu; Fuji Astuti; Yuliasma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Evaluation in dance is often viewed as a subjective process that is difficult to standardize. This study aims to reformulate the definition of evaluation in the context of dance by considering pedagogical and professional aspects. Using qualitative methods through literature studies, this study analyzes various aesthetic theories and art criticism to find essential elements in the assessment of dance works. The results show that dance evaluation is a reflective-analytical process involving technical description, formal analysis, and interpretation of meaning. This definition shifts the evaluation paradigm from mere numerical assessment to a critical dialectic that bridges the choreographer's artistic vision with audience appreciation. The conclusion of this study emphasizes that a robust definition of evaluation is essential to ensure objectivity and improve the quality of contemporary dance development.